Pembuatan Alat Angkut Tradisional Berbasis Bahan Bekas untuk Membantu Kelompok Tani di Lahan Gambut Kabupaten Pulang Pisau - Abustan Abustan; Wiyogo Wiyogo; Jhonni Rentas Duling (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Oil palm plantations on peatlands have a high acidity level and have an unstable soil structure. In the rainy season, the land surface tends to be slippery and stick to vehicle footwear or tires. While in the dry season, the soil is dry, flammable, and dusty, especially if it is passed by a four-wheeled vehicle with a significant weight and size. Farmers transport the harvest of palm fruit using a small size conveyance, a type of “arco” capacity 50-70 kg, plastic drum capacity 40-50 kg, and peninsula capacity 30-40 kg. The process of transporting palm fruit from harvest to the mill takes a long time, potentially harming farmers due to “restan fruit” (palm oil is loose from the stem). The leading cause is the conveyance that is used in small volumes and is done by human labor. Palm fruit to stay fresh arrived at the processing plant with a duration of no more than 2 x 24 hours, if late farmers experience a loss of 10-15% because the weight of the scales is shrinking. The innovation of traditional conveyance capacity 500-750 kg based on used materials has been carried out using a special design that takes into account the carrying capacity, labor, road conditions, and timeliness so that the fruit does not become “restan.” Farmers are much helped both in terms of energy, process (time), transport volume, and can be operated on peatlands in both the rainy or dry season.